Implementation Strategy for Project Based Learning Based on Islamic Values in Early Childhood Education - Tussadiyah, Halimah; Wirdatunnabilah; Hasanah, Lathipah; Rahmadini, Putri Fauziah (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
This study aims to explain the strategy for implementing the project-based learning model (PjBL) in early childhood education (ECE) in the context which is oriented towards Islamic values. PjBL allows children to actively participate through challenging projects and close to everyday life, thus encouraging critical thinking, collaboration, communication, and creativity skills from an early age. At the same time, PjBL can be a vehicle for instilling manners, morals, social responsibility, and gratitude for Allah's creation through authentic and meaningful learning experiences. This study uses a literature study method by examining articles, scientific journals, and documents related to the implementation of PjBL in ECE. The results of the study show that PjBL can be effectively implemented through targeted project planning, strengthening the role of teachers as facilitators as well as role models, and active involvement of children at each stage of the project (planning, implementation, reflection, and follow-up). These findings are expected to provide insight for ECE educators to improve the quality of active, holistic, and worship-worthy learning, so that children grow up to be creative people with faith and noble character.